Measurements of 177mLu contaminants in Lutetium-Based Therapeutics - D. Coll Segarra; S. Arias Soriano; S.V. Tipnis; J.A. Nye (Health Physics, 2026)
INTRODUCTION: A practical approach is presented to reliably detect and quantify the long-lived contaminant 177m Lu commonly found in 177 Lu-based therapeutics. OBJECTIVE: The objective of this work was to provide methods to measure 177m Lu on detector systems typically found in hospital environments that support theranostic programs. METHODS: Twenty-four samples (14 177 Lu dotatate, 10 177 Lu PSMA) were collected from unused patient vials. 1-mL aliquots were drawn from each vial for counting on a well-type, one-inch (2.5-cm) NaI detector and liquid scintillation counter (LSC) system that support the hospital theragnostic and radiation safety programs, respectively. Prior to measurement, all samples were counted on a well-type high-purity germanium detector (HPGe) to establish a quantification standard for comparison. All detectors were calibrated with known standards and counting durations were adjusted to achieve